Digital Literacy Integration in Biology Education: A Systematic Literature Review on Effectiveness and Implementation Challenges - Edo Wijaya; Ahmad Shahroni; Tisya Selviani Ariyanti; Destiara Nabilla (ISEJ : Indonesian Science Education Journal, 2025)
This study examines the integration of digital literacy in biology learning through a systematic analysis of research articles published between 2019 and 2024. The aim of this review is to identify its effectiveness, explore the associated challenges, and formulate implementation patterns of digital literacy in enhancing the quality of biology education. The findings indicate that digital literacy contributes positively to improving students’ cognitive learning outcomes and higher-order thinking skills. The ability to access, manage, and evaluate digital information has been shown to support a deeper understanding of complex biological concepts. In addition, the integration of digital literacy through innovative learning models such as STEM, HOTS-oriented instruction, and problem-based learning enhances student engagement and active participation in the learning process. However, the implementation of digital literacy continues to face several challenges, including limited infrastructure, disparities in digital competencies among students, and variations in teachers’ ability to integrate technology effectively. These findings highlight that the effectiveness of digital literacy is strongly dependent on the quality of instructional design and the readiness of the educational ecosystem. Therefore, a more integrated and sustainable approach is required to optimize the role of digital literacy in biology learning, ensuring that it remains adaptive and relevant to the demands of 21st-century education.